On the Dynamics of Two-Dimensional Capillary-Gravity Solitary Waves with a Linear Shear Current - Dali Guo; Bo Tao; Xiaohui Zeng (Advances in Mathematical Physics)
The numerical study of the dynamics of two-dimensional capillary-gravity solitary waves on a linear shear current is presented in this paper. The numerical method is based on the time-dependent conformal mapping. The stability of different kinds of solitary waves is considered. Both depression wave and large amplitude elevation wave are found to be stable, while small amplitude elevation wave is unstable to the small perturbation, and it finally evolves to be a depression wave with tails, which is similar to the irrotational capillary-gravity waves.